Genetics of humoral and cytokine activation in heart failure and its importance for risk stratification of patients - Spinarová, L; Spinar, J; Vasků, A; Pávková-Goldbergová, M; Ludka, O; Tomandl, J; Vítovec, J (Experimental and molecular pathology, 2008)
The study objective is to prove an association among plasma concentration of big endothelin and endothelin-1, other clinical parameters and two frequent polymorphisms - G8002A and -3A/-4A - in the endothelin-1 (EDN-1) coding gene (6p21-23), and among plasma concentration of TNF alpha and gene polymorphisms TNF alpha -308 A/G, -238 A/G, TNF beta Ncol and 3'TACE (tumour necrosis factor alpha converting enzyme) in patients with chronic heart failure (CHF). The second objective is to find an association between polymorphisms G8002A and -3A/4A EDN-1 with diabetes mellitus (DM), peripheral artery disease (PAD) and myocardial infarction (MI) in patients with chronic heart failure (CHF). The study population included 266 patients with symptomatic CHF and proven dysfunction of the left ventricle (LV). Genotyping and plasma concentrations of humoral substances were examined in 224 patients with ejection fraction (EF) below 40%. No associations between plasma concentrations of endothelin-1 and big endothelin and polymorphisms G8002A (p=0.87, p=0.81) and -3A/-4A (p=0.871, p=0.749) in the gene coding endothelin-1 were found. No associations were observed between plasma concentration of TNF alpha and genotypes in four polymorphisms in TNF alpha, beta and TACE genes. A significant correlation was seen between plasma concentration of big endothelin and pulmonary congestion. Patients with ischemic heart disease (IHD) and previous MI showed a difference in the distribution of genotype G8002A for endothelin-1: allele G 0.718 and A 0.282 vs those without MI: allele G 0.882 and A 0.118, (p<0.05). Patients with IHD and DM had allele G in 0.67 and A 0.33, while those without DM had allele G in 0.790 and A in 0.209 (p<0.03). Patients with IHD and concomitant PAD had allele G in 0.718 and A in 0.282 vs those without PAD allele G in 0.882 and A in 0.118 (p<0.0004). Patients with dilative cardiomyopathy (DCMP) showed no differences in genotype G8002A and presence of DM or PAD. It might be speculated that in the case of endothelin-1 and TNF alpha in CHF the genetic determination is not important, and plasma concentrations are influenced more by the disease severity. Ischemics with previous MI, concomitant DM or PAD showed more frequently allele A and less often allele G than those without these diseases. A genotype with allele A is associated with higher risk of concomitant diseases.
Keywords: Genetic Predisposition to Disease; diabetes mellitus; Chronic Disease; cytokiny; chronická nemoc; Risk Assessment; Middle Aged; Diabetes Mellitus; mužské pohlaví; infarkt myokardu; Cytokines; Endothelin-1; endotelin-1; polymorfismus genetický; Myocardial Infarction; onemocnění periferních cév; Polymorphism, Genetic; Peripheral Vascular Diseases; ženské pohlaví; hodnocení rizik; Humans; biologické markery; lidé středního věku; srdeční selhání; Biomarkers; genetická predispozice k nemoci; Female; Heart Failure; lidé; Male